How is cognitive behavioural therapy for insomnia delivered to adults with comorbid persistent musculoskeletal pain and disordered sleep? A scoping review. - Abigail Browne; Roisin Cahalan; Kieran O' Sullivan (PLoS ONE)
Background Disordered sleep and persistent musculoskeletal pain are highly comorbid. Behavioural interventions such as Cognitive Behavioural Therapy for Insomnia (CBT-I) have shown promise in the management of both disordered sleep and persistent musculoskeletal pain. The aim of this review was to examine how CBT-I is delivered in randomised controlled trials involving people with comorbid disordered sleep and persistent musculoskeletal pain. Methods The protocol for this scoping review was registered with the Open Science Framework. Electronic searches of ten database and three clinical trials registries were performed up to 25 October 2023. The methodological quality of each study was evaluated by two independent reviewers using the PEDro tool. The reporting of CBT-I interventions was evaluated using the Template for Intervention Description and Replication (TIDieR) checklist. Results Twelve studies met the eligibility criteria. TIDieR scores ranged from 7-11/12, with a mean score of 8.8/12. CBT-I always involved two core components-sleep restriction and stimulus control. Furthermore, an additional five components were usually involved-a cognitive component, sleep hygiene, sleep education, relaxation/deactivation procedures and relapse planning. There was also considerable consistency in the frequency (weekly) and duration (5-9 weeks) of CBT-I programmes. Aspects inconsistently reported included who delivered the intervention; what modifications were made, if any; and the session content and duration. PEDro scores ranged from 5-8/10, with a mean score of 6.7/10. Conclusions These findings demonstrate considerable consistency in the components of CBT-I delivered in clinical trials along with the number of sessions. The frequency of sessions was also consistent where almost all studies held weekly session. However, some aspects were either not reported (e.g., precise content of components) or inconsistent (e.g., use of terminology). CBT-I was delivered both individually and in groups. Greater consistency, and more detailed reporting regarding who delivered the intervention, the training provided, and the specific content of CBT-I components would add clarity, and may enhance CBT-I efficacy and allow better replication.